2015
DOI: 10.1177/1359105315573448
|View full text |Cite
|
Sign up to set email alerts
|

Food cravings mediate the relationship between chronic stress and body mass index

Abstract: This study examined the relationships between chronic stress, food cravings, and body mass index. A community-based sample of adults (N = 619) completed a comprehensive assessment battery and heights and weights were measured. Chronic stress had a significant direct effect on food cravings, and food cravings had a significant direct effect on body mass index. The total effect of chronic stress on body mass index was significant. Food cravings partially mediated the relationship between chronic stress and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 57 publications
4
56
0
6
Order By: Relevance
“…The present study detected depression release and shifting of psychological needs satisfaction from Internet to real life significantly predict craving amelioration at both post-intervention and 6-month follow-up. Similarly, many previous researches have observed the mediation effect of craving amelioration on the relationship between negative emotion (e.g., depression) or stress and severity of addiction in substance use disorders (Witkiewitz and Bowen, 2010; Witkiewitz et al, 2011) and behavioral disorder (Chao et al, 2015). Recent review studies have hypothesized a framework of craving-as-emotion that various affective states can precipitate cravings and varies according to context (Heckman et al, 2013; Sayette, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…The present study detected depression release and shifting of psychological needs satisfaction from Internet to real life significantly predict craving amelioration at both post-intervention and 6-month follow-up. Similarly, many previous researches have observed the mediation effect of craving amelioration on the relationship between negative emotion (e.g., depression) or stress and severity of addiction in substance use disorders (Witkiewitz and Bowen, 2010; Witkiewitz et al, 2011) and behavioral disorder (Chao et al, 2015). Recent review studies have hypothesized a framework of craving-as-emotion that various affective states can precipitate cravings and varies according to context (Heckman et al, 2013; Sayette, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…Since stress is linked to eating habits and obesity, a further exploration of a combination of these two approaches may be warranted. Stress is a significant contributor to non-homeostatic caloric intake and food has been indicated as a preferred self-medication method in response to chronic stress [19,45]. Thus, addressing stress levels and increasing stress resilience in the context of the obesity treatment may have much more profound as well as sustained effects than behavioral intervention alone.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies as well as animal studies may provide insight into the underlying neural mechanisms that control emotional eating. Recent evidence in humans however suggests a direct link from the hypothalamus into the dorsal and ventral striatum, brain regions typically associated with reward and satiety [19, 46]. Furthermore, studies have shown that VTA neurons contain melanocortin (MC4) receptors, which are known to be key regulators of food intake and weight gain [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations